Single-dose of adrecizumab versus placebo in acute cardiogenic shock (ACCOST-HH): an investigator-initiated, randomised, double-blinded, placebo-controlled, multicentre trial. Issue 3 (March 2022) - Karakas, Mahir; Akin, Ibrahim; Burdelski, Christoph; Clemmensen, Peter; Grahn, Hanno; Jarczak, Dominik; Keßler, Mirjam; Kirchhof, Paulus; Landmesser, Ulf; Lezius, Susanne; Lindner, Diana; Mebazaa, Alexandre; et al.
Summary: Background: Cardiogenic shock has a high mortality on optimal therapy. Adrenomedullin is released during cardiogenic shock and is involved in its pathophysiological processes. This study assessed treatment with the humanised, monoclonal, non-neutralising, adrenomedullin antibody adrecizumab, increasing circulating concentrations of adrenomedullin in cardiogenic shock. Methods: In this investigator-initiated, placebo-controlled, double-blind, multicentre, randomised trial (ACCOST-HH), patients were recruited from four university hospitals in Germany. Patients were eligible if they were 18 years old or older and hospitalised for cardiogenic shock within the last 48 h. Exclusion criteria were resuscitation for longer than 60 min and cardiogenic shock due to sustained ventricular tachycardia or bradycardia. Adult patients in cardiogenic shock were randomly assigned (1:1) to intravenous adrecizumab (8 mg/kg bodyweight) or placebo using an internet-based software. A block randomisation procedure was applied with stratification by age (older vs younger than 65 years), sex (male vs female), and type of underlying cardiogenic shock (acute myocardial infarction vs other entities). Investigators, patients, and medical staff involved in patient care were masked to group assignment. The primary endpoint was number of days up to day 30 without the need for cardiovascular organ support, defined as vasopressor therapy, inotropes, or mechanical circulatory support (or both) assessed in the intention-to-treat population. Safety outcomes included therapy-emergent serious adverse events, severe adverse events, adverse events, suspected unexpected serious adverse reactions, study drug-related mortality, and total mortality. The trial was registered at ClinicalTrials.gov, NCT03989531, and EudraCT, 2018-002824-17, and is now complete. Findings: Between April 5, 2019, and Jan 13, 2021, 150 patients were enrolled: 77 (51%) were randomly assigned to adrecizumab and 73 (49%) to placebo. All patients received the allocated treatment. The number of days without the need for cardiovascular organ support was not different between patients receiving adrecizumab or placebo (12·37 days [95% CI 9·80–14·94] vs 14·05 [11·41–16·69]; adjusted mean difference −1·69 days [–5·37 to 2·00]; p=0·37). Serious adverse events occurred in 59 patients receiving adrecizumab and in 57 receiving placebo (odds ratio 0·92 [95% CI 0·43–1·98]; p=0·83). Mortality was not different between groups at 30 days (hazard ratio 0·99 [95% CI 0·60–1·65]; p=0·98) or 90 days (1·10 [0·68–1·77]; p=0·71). Interpretation: Adrecizumab was well tolerated in patients with cardiogenic shock but did not reduce the need for cardiovascular organ support or improve survival at days 30 and 90. Funding: Adrenomed AG and University Hospital of Hamburg